# If h(x) = x^3+ x and g(x) = 2x + 3, then g(h(2)) = ?

### 2 Answers | Add Yours

We have the two functions h(x) = x^3+ x and g(x) = 2x + 3.

Now we need to find g(h(2)).

h(2) = 2^3 + 2

= 8 + 2

= 10

g(h(2))

= g(10)

= 2*10 + 3

= 20 + 3

= 23

**Therefore g(h(2)) = 23.**

Given that:

h(x) = x^3 + x

g(x) = 2x+ 3

We need to find g(h(2))

First we will determine the values of h(2).

==> h(2) = 2^3 + 2 = 8+2 = 10

Now we will substitute into g(h(2)

==> g(h(2)) = g(10)

Now we will substitute into g(x).

==> g(10) = 2*10 + 3 = 23

**==> g(h(2)) = 23**